Controlling errors in unidosis carts - Inmaculada Díaz Fernández; Clara Fernández-Shaw Toda; David García Marco (Fundación para el Desarrollo de la Enfermería, 2010)
Objective: To identify errors in the unidosis system carts. Method: For two months, the Pharmacy Service controlled medication either returned or missing from the unidosis carts both in the pharmacy and in the wards. Results: Uncorrected unidosis carts show a 0.9% of medication errors (264) versus 0.6% (154) which appeared in unidosis carts previously revised. In carts not revised, the error is 70.83% and mainly caused when setting up unidosis carts. The rest are due to a lack of stock or unavailability (21.6%), errors in the transcription of medical orders (6.81%) or that the boxes had not been emptied previously (0.76%). The errors found in the units correspond to errors in the transcription of the treatment (3.46%), non-receipt of the unidosis copy (23.14%), the patient did not take the medication (14.36%)or was discharged without medication (12.77%), was not provided by nurses (14.09%,) was withdrawn from the stocks of the unit (14.62%), and errors of the pharmacy service (17.56% ). Conclusions: It is concluded the need to redress unidosis carts and a computerized prescription system to avoid errors in transcription.Discussion: A high percentage of medication errors is caused by human error. If unidosis carts are overlooked before sent to hospitalization units, the error diminishes to 0.3%.